Analiza porównawcza dochodów w powiatach podregionu ostrołęcko-siedleckiego - Ginter, Agnieszka (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The paper aims to analyze the revenues of ten districts of ostrołęckosiedlecki subregions located in in the Mazovia voivodship in the period of two years, means 2006 and 2007. The paper presents the total revenue structure of the ostrołęcko-siedlecki subregion, such as the revenue structure in ten districts of this subregion. The paper shows the sources of revenue in chosen subregion as well as in the disrticts